(In)justice on Ice: Valieva and International Sport Governing Bodies' Justice Duties Toward Underage Athletes. Issue 1 (2nd January 2023) - Diaz, Brett; Campos, Marcus; Škerbić, Matija; Mallett, Cam; Lopez Frias, Francisco Javier
ABSTRACT: After two years of discussions and revisions, the World Anti-Doping Agency (WADA) published the 2021 World Anti-Doping Code on June 16, 2020. Among the most significant additions to this iteration of the Code was the inclusion of new categories of athletes subject to differential treatment by WADA, including the "protected person" category. In this paper, we examine the recent case of figure skater Kamila Valeryevna Valieva, the first athlete given differential treatment due to her being categorized as a "protected person." We apply a relational justice framework to the case to provide a nuanced, descriptive analysis of the case generally, and the application of the "protected person" category in particular.We first describe details of the athlete, her performances and anti-doping rule violation, and the "protected person" category, to provide context. We then describe and analyze the relations between several institutional actors, principally WADA and the International Court for the Arbitration of Sport (CAS), the athlete and her team, and other figure skating athletes at the Beijing Winter Olympic Games. To do so, we use two concepts of justice, conservative and ideal, and their component parts, entitlement, desert, and need.Our description and analyses demonstrate that (1) WADA's notions of justice are essentially conservative, while CAS acted toward more ideal notions, creating a fundamental disagreement in what was owed and to whom. We show (2) that CAS' decision may have nonetheless caused harm to the athlete, raising questions about the efficacy and capability of the "protected person" category. Finally, (3) our analyses show the influence that notions of justice necessarily have these actors shape each other, thus change the sporting institutions and activities themselves.